Comparison of transvaginal sacrospinous ligament fixation with abdominal sacrocolpopexy in treatment of post-hysterectomy vault prolapse-a prospective randomized study - Dash, Kamal Kumar; Dasgupta, Anjan; Pal, Abirbhab; Chakraborty, Ayantika; Dash, Barsarani; Ghosh, Partha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Vaginal vault prolapse is a common condition following abdominal or vaginal hysterectomy causing negative impact on women’s quality of life. The study compares the efficacy of abdominal and vaginal route surgery in correcting post-hysterectomy vault prolapse by postoperative assessment and at least twelve months follow up. Methods: A prospective comparative study among post-hysterectomy patients attending the GOPD of Midnapore Medical College diagnosed as vaginal vault prolapse at least stage2 between January 2013 to December 2019. The study population included 31 women divided into two groups-group A included 16 women underwent unilateral sacrospinous ligament fixation (SSF) and group B included 15 women underwent abdominal sacrocolpopexy (ASC). Results: There was no significant difference between the two groups in terms of mean age, mean weight, mean parity and BMI, hence both groups are comparable. The mean operating time was 117±19.68 min in ASC group and 83.25±11.28 min in SSF group (p<0.005); significant mean blood loss was reported in ASC group (373±97.79 ml in ASC group versus 193.125±98.97 ml in SSF group, p<0.005), more hospital stays in ASC group (p<0.005) and more post operative complications in ASC group than SSF group. At follow up, the mean vaginal length showed significantly longer for ASC group than that of SSF group (p<0.005). Conclusions: ASC and SSF, both techniques are effective in management of vault prolapse in hands of an expert though recovery time is much quicker in SSF group.